Assisting Hearing and Physically Impaired Students in Navigating Immersive Virtual Reality for Library Orientation - Pakinee Ariya; Yakannut Yensathit; Phimphakan Thongthip; Kannikar Intawong; Kitti Puritat (Technologies, 2024)
This study aims to design and develop a virtual reality platform (VR-ISLS) tailored to support hearing and physically impaired students at the university library for navigating and utilizing library services. By employing an immersive virtual environment, the platform replicates the physical setting of the university’s library to create a realistic experience that reduces anxiety and enhances familiarity. The platform integrates assistive technology functions, including sign language interpretation, customizable audio cues, vibration feedback, and various locomotion controls to meet the diverse needs of impaired students. The research methodology employs an iterative development process, incorporating feedback from library staff, disability support services, and students to ensure usability and accessibility. Evaluation of the platform using the System Usability Scale (SUS) and user feedback revealed a positive reception, with recommendations for further customization and enhanced assistive features to optimize the user experience. This study underscores the importance of inclusive design and continuous iteration in creating immersive virtual reality tools that provide significant benefits for persons with disabilities, enhancing both accessibility and learning experiences.